Reduction of Damage Concentration in Seismic Retrofitted RC Building with Friction Dampers - Terapat Sirinipitakul; Rawirot Suwannatrai; Hnin Hnin Hlaing; Panumas Saingam (My University, 2024)
Because of their lack of lateral force resistance or energy dissipation capability, reinforced concrete (RC) structures have suffered significant damage in previous earthquakes.There is a demand to develop and improve the seismic performance of vulnerable existing RC buildings, particularly those not initially designed for seismic events or designed to an outdated seismic standard.Seismic retrofit of RC buildings using friction dampers is an innovative method to improve the seismic performance of the structures.In this study, nonlinear response history analysis was performed to investigate and compare the seismic performance of retrofitted buildings.The numerical results suggest that the maximum displacement was substantially improved after retrofitting the existing RC building with friction dampers.The damage concentration of the retrofitted buildings with friction dampers is reduced significantly when compared to the existing RC buildings.
Keywords: Seismic Performance and Analysis